PENGELOLAAN DAERAH RAWAN BENCANA ALAM LETUSAN GUNUNG GEDE DI KAWASAN PUNCAK KABUPATEN CIANJUR - -, Bombom Rachmat Suganda (Bulletin of Scientific Contribution, 2011)
The northern part Cianjur based on the Regional Hazard Map of Mount Gede in West Java (kaswanda, 1994) is an explosion hazard areas. The rapid economic development, especially in the tourism sector resulting in increased occupancy, hotel or villa. As a result of the growth area of the building, and the increase of population, and transfer of land use, has resulted in the handling of the impact so that the necessary pre-disaster management in which one of them is a disaster mitigation. Determination of the level of risk is one basis for determining mitigation measures related to spatial planning. The main risk factors of natural disasters include volcanic eruption hazard factors, vulnerability and resilience. Factors will affect the hazard mitigation measures that will be done in the danger area. The primary hazard mitigation in the area would have been different in the secondary area. Thus the delineation is an important step that must be done before determining the level of risk. Determination of the spatial areas prone to natural disasters Volcanic eruptions, can be done with the mitigation measures related to spatial planning based on risk level.